2018
DOI: 10.1002/jib.508
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional profiling of amino acid supplementation and impact on aroma production in a lager yeast fermentation

Abstract: The objective of this study was to investigate the effect of adding selected amino acids (glutamate, proline, lysine and valine) to brewing wort on the generation of aroma active compounds along with the transcriptional profiling of genes involved in nitrogen regulation. The results showed that changes in the amino acid levels had no significant impact on the general course of fermentation except for the addition of lysine, which prolonged the period that lager yeast was in suspension. Flavour profile of lager… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…However, quality problems such as bitterness and consumer discomfort can occur when higher alcohols exceed the legal limit (60). Further, in a study with Saccharomyces cerevisiae, Yin et al indicated that leucine, valine, glutamate, phenylalanine, serine and lysine were closely related to the production of ester compounds and found that the aroma compounds could be modified by adding amino acids (60,61). Susanne et al considered the relationship between amino acid composition and higher alcohols and esters in a synthetic medium fermented by different Saccharomyces cerevisiae strains (62).…”
Section: Effects Of Nitrogenous Compounds On Microbial Growth and Met...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, quality problems such as bitterness and consumer discomfort can occur when higher alcohols exceed the legal limit (60). Further, in a study with Saccharomyces cerevisiae, Yin et al indicated that leucine, valine, glutamate, phenylalanine, serine and lysine were closely related to the production of ester compounds and found that the aroma compounds could be modified by adding amino acids (60,61). Susanne et al considered the relationship between amino acid composition and higher alcohols and esters in a synthetic medium fermented by different Saccharomyces cerevisiae strains (62).…”
Section: Effects Of Nitrogenous Compounds On Microbial Growth and Met...mentioning
confidence: 99%
“…For example, for beer, the raw materials need to be gelatinised, liquefied and saccharified before fermentation and then fermented by yeast. However, the impact of nitrogenous compounds are reflected in yeast metabolism and flavour and aroma of the beer (60)(61)(62). Other fermented grain beverages, such as hongqu rice wine, rice liquor and sake, have complex production processes.…”
Section: Effects Of Nitrogenous Compounds On Fermented Liquormentioning
confidence: 99%